2020
DOI: 10.2147/ijn.s248741
|View full text |Cite
|
Sign up to set email alerts
|

<p>Osteoimmune Modulation and Guided Osteogenesis Promoted by Barrier Membranes Incorporated with S-Nitrosoglutathione (GSNO) and Mesenchymal Stem Cell-Derived Exosomes</p>

Abstract: Background: The use of polycaprolactone (PCL) for bone defects in a clinical setting is limited due to a lack of bioactivity. Exosomes derived from mesenchymal stem cells (MSCs) have an important immunoregulatory potential and together with S-nitrosoglutathione (GSNO) they possess therapeutic potential for bone regeneration. Materials and Methods: In this study, PCL was modified with GSNO and MSC-derived exosomes and the impact on macrophages and osteogenes is evaluated. Results: MSC-derived exosomes exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 58 publications
0
14
0
5
Order By: Relevance
“…Although BMSC-EVs have shown great potential in bone metabolic diseases, there are still a series of problems to be further elucidated, such as purification, mass production, identification, transportation, the preservation of exosomes and their half-life and long-term safety in vivo. One of the most important issues is that the administration concentration and dosage of exosomes have not been unified [ 177 ]. Regrettably, EVs at different concentrations were not used to explore the dose-effect of exosomes, and even the administration concentration and dose of exosomes were not described in detail in most of the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Although BMSC-EVs have shown great potential in bone metabolic diseases, there are still a series of problems to be further elucidated, such as purification, mass production, identification, transportation, the preservation of exosomes and their half-life and long-term safety in vivo. One of the most important issues is that the administration concentration and dosage of exosomes have not been unified [ 177 ]. Regrettably, EVs at different concentrations were not used to explore the dose-effect of exosomes, and even the administration concentration and dose of exosomes were not described in detail in most of the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…There are various types of scaffolds in BTE, including collagen sponge scaffolds [ 95 ], β-TCP scaffolds [ 22 ], hydroxyapatite (HA) scaffolds [ 14 ], calcium sulfate cement scaffolds [ 96 ], bioactive glass [ 41 ], polycaprolactone (PCL) scaffolds [ 97 ], and other innovative synthetic scaffolds [ 19 ], which should be selected appropriately according to their different properties when applied to the regeneration of bone defects. For example, compared with other bone substitutes, the translucent collagen sponge is an ideal scaffold for the detection of MSC-Exos in periodontal tissue regeneration and is commonly used as a scaffold material for carrying Exos in periodontal defect models [ 98 ].…”
Section: Application Of Msc-evs In Bone Defectsmentioning
confidence: 99%
“…It has been reported that exosomes play a role in inflammation modulation. For example, MSC-derived exosomes can promote macrophage polarization toward the M2 phenotype and inhibit the inflammatory response, indicated by the reduced gene and protein expression of inflammatory cytokines, such as IL-6 and TNF-α ( Guan et al, 2022 ; Jiang et al, 2021 ; Lu et al, 2021 ; Wang X. et al, 2020 ). Research shows that MSC-derived exosomes promote macrophage M2 polarization via the NF-κB pathway ( Fan et al, 2021 ).…”
Section: Applications Of Bone Engineering Scaffolds With Exosomes In ...mentioning
confidence: 99%